Bacillus niameyensis sp. nov., a new bacterial species isolated from human gut. (November 2015) - Tidjani Alou, M.; Rathored, J.; Traore, S.I.; Khelaifia, S.; Michelle, C.; Brah, S.; Diallo, B.A.; Raoult, D.; Lagier, J.-C.
Abstract: Bacillus niameyensis sp. nov. strain SIT3 T (= CSUR P1266 = DSM 29725) is the type strain of B. niameyensis sp. nov. This Gram-positive strain was isolated from the digestive flora of a child with kwashiorkor and is a facultative anaerobic rod and a member of the Bacillaceae family. This organism is hereby described alongside its complete genome sequence and annotation. The 4  286  116 bp long genome (one chromosome but no plasmid) contains 4130 protein-coding and 66 RNA genes including five rRNA genes.